THE EXISTENCE OF COMMUNITIES’ HUMAN RIGHTS IN MINING AREAS - Amrianto, Andika Dwi; Ramdan, Muhammad; Yusmi, Tsania (Faculty of Law Atma Jaya Yogyakarta University, 2025)
This research is used to answer two problem formulations. First, what is the human rights approach to overcoming the dangers of mining in Indonesia. Second, how is law enforcement against the negative impacts of mining in Indonesia. The research method used in normative juridical research. The data used is secondary data by examining primary legal materials in the form of statutory regulations related to this issue and secondary legal materials in the form of articles or scientific papers, as well as tertiary legal materials. This research was analyzed using qualitative descriptive analysis after the data was obtained. The results of this research focus on two conclusions. The state is primarily obligated to protect and respect human rights as the fundamental rights of every individual. International legal instruments such as the ICCPR, UDHR, and CAT regulate state obligations regarding human rights, while at the national level, they are regulated in statutory regulations. As a legal state, Indonesia is also obliged to protect human rights, including the right to live in prosperity, a good and healthy environment, and health services. Mining is an activity that has a direct impact on the environment. Although the mining sector contributes to state income and employment, it is often associated with problems of environmental degradation. Administrative sanctions that can be imposed for violations in mining include written warnings, fines, temporary suspension of activities, and revocation of permits. The Minerba Law also regulates criminal sanctions, including imprisonment and fines.